2015
DOI: 10.1063/1.4922143
|View full text |Cite
|
Sign up to set email alerts
|

Spectral interference of terahertz pulses from two laser filaments in air

Abstract: Spectral interference is experimentally demonstrated by two terahertz pulses emitting from filaments induced by two successive femtosecond laser pulses in air. Here a leading pulse is set to be weaker than a trailing pulse and their temporal separation is larger than the pulse duration of the terahertz pulses. When the leading pulse is stronger than the trailing pulse, the frequency modulation within the whole terahertz envelope is greatly deteriorated due to nonlinear effects applying on the trailing pulse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The result is shown in Fig. 7(b) 110 . It can be found that the THz spectrum spans to ~20 THz with a higher SNR.…”
Section: Thz Spectrummentioning
confidence: 95%
“…The result is shown in Fig. 7(b) 110 . It can be found that the THz spectrum spans to ~20 THz with a higher SNR.…”
Section: Thz Spectrummentioning
confidence: 95%
“…Such a PC can control the polarization and phase of each optical beam individually for coherent control of the THz emission [11] . THz wave emission from biased gas plasma or plasma filaments in ambient air can be classified to the case of single-wavelength laser excitation [20,22,25,46,66,6979] . The use of single-color few-cycle laser pulses to ionize gases for intense THz wave emission can be classified into both cases [80] , since, very similar to the asymmetric optical fields synthesized from two-color optical fields, a few-cycle laser field itself can produce asymmetric fields by properly controlling the carrier–envelope phase without the involvement of the SH laser field.…”
Section: Plasma-based Thz Wave Photonics In Gas Phasementioning
confidence: 99%
“…6,7 However, the lack of the frequency selecting and tuning methods for this source impedes its wider application. Some efforts have been made to achieve the frequency tunable THz source, for instance, by using two filaments 8,9 or adding the external cavity. 10,11 Actually, THz wave generated from two-color filament covers ultra broadband frequency range, filling up the entire "THz gap" from 0.1 to 10 THz.…”
Section: Introductionmentioning
confidence: 99%